PROFIL PENYALAHGUNAAN OBAT DEKSTROMETORFAN PADA MASYARAKAT DI KECAMATAN TOMBARIRI TIMUR KABUPATEN MINAHASA - Roringpandey, Meriam Brigitha (UNIVERSITAS SAM RATULANGI, 2013)
The dose of dextrometorphan often misused by some people. Excessive doses ofdextrometorphan gives euphoria feeling, sense of calm, sight and hearing hallucination. Theaim of this research was to find out the profile of dextrometorphan abused on sub district EastTombariri Society, Minahasa Regency. This research is a descriptive research. The researchusing interview method to 50 respondents which given 7 same and structured question oneach respondents. The result shows that dextrometorphan abuse was occurred among youth insub district East Tombariri Society, Minahasa Regency. Information about dextromethorphanwere the knowledge to obtained drugs which did not fit distribution procedure and thepurpose of drug uses to relieve stress. Dextrometorphana can be consumed a few youth grainsper day and usually combined with alcohol drinks to accelerate the desired effect such asincrease confidence, happiness, reduce burden, and free feeling.Key words : Drug abuse, Dextrometorphan, East Tombariri, Interview